2013
DOI: 10.7860/jcdr/2013/6509.3781
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Outcome in Meconium Stained Deliveries

Abstract: Meconium stained amniotic fluid is really worrisome from both, obstetrician's and paediatrician's points of view, as it increases the caesarean rates, causes birth asphyxia, MAS and increases neonatal intensive care unit admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
75
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 7 publications
19
75
7
Order By: Relevance
“…16 Regarding mode of delivery, most studies have found a higher caesarean section rate. 1,5,11 Shaikh EM found it was not uncommon for obstetricians to be more aggressive in labors with meconium stained amniotic fluid leading to higher caesarean section rate, which was 82% in their study. 17 In contrast the caesarean section rate in the clear liquor group was 18% (82% vs 18% P<0.05).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…16 Regarding mode of delivery, most studies have found a higher caesarean section rate. 1,5,11 Shaikh EM found it was not uncommon for obstetricians to be more aggressive in labors with meconium stained amniotic fluid leading to higher caesarean section rate, which was 82% in their study. 17 In contrast the caesarean section rate in the clear liquor group was 18% (82% vs 18% P<0.05).…”
Section: Discussionmentioning
confidence: 93%
“…Sample size was calculated using Epi-Info software, and using NICU admission rate as outcome to be studied in cases and controls. 1 Fetal heart rate abnormalities were documented as per current recommendations. 6 Cases and controls were selected on the basis of following inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Factors such as placental insufficiency, maternal hypertension, pre-eclampsia, oligohydramnios or maternal drug abuse (tobacco, cocaine) result in In utero passage of meconium. [3] so theexistence of MSAF in other circumstances is a marker of fetal distress and may be associated with adverse fetal and neonatal outcome [4,5] . The strong relationship of stillborn infants, abnormal FHR tracings, neonatal encephalopathy, respiratory distress (Meconium aspiration syndrome, MAS) and abnormal neurological outcome with presence of MSAF has been testified in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Other studies have found incidence rate as low as 3.03% to as high as 18%. 1,2,10,11 This probably reflects the level of antenatal care in different places where these studies were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…1 The passage of meconium may simply represent the normal physiological in-utero gastrointestinal maturation process or it may indicate an acute or chronic hypoxic event, thus making it a warning sign of fetal compromise. 2 Meconium aspiration syndrome (MAS) may be defined as a respiratory distress which develops shortly after birth with radiographic evidence of aspiration pneumonitis in the presence of meconium stained amniotic fluid(MSAF). 3,4 In addition to it, the rate of severe mental retardation and cerebral palsy is significantly higher among surviving infants born with MAS.…”
Section: Introductionmentioning
confidence: 99%